Contribution of the PALB2 c.2323C>T [p.Q775X] Founder mutation in well-defined breast and/or ovarian cancer families and unselected ovarian cancer cases of French Canadian descent - Tischkowitz Marc; Sabbaghian Nelly; Hamel Nancy; Pouchet Carly; Foulkes William D; Mes-Masso; Provencher Diane M; Tonin Patricia N (BMC, 2013)
Abstract Background The PALB2 c.2323C>T [p.Q775X] mutation has been reported in at least three breast cancer families and breast cancer cases of French Canadian descent and this has been attributed to common ancestors. The number of mutation-positive cases reported varied based on criteria of ascertainment of index cases tested. Although inherited PALB2 mutations are associated with increased risks of developing breast cancer, risk to ovarian cancer has not been fully explored in this demographically unique population. Methods We screened the PALB2 p.Q775X variant in 71 families with at least three cases of breast cancer (n=48) or breast and ovarian cancers (n=23) that have previously been found negative for at least the most common BRCA1 and BRCA2 mutations reported in the French Canadian population and in 491 women of French Canadian descent who had invasive ovarian cancer and/or low malignant potential tumors of the major histopathological subtypes. Results We identified a PALB2 p.Q775X carrier in a breast cancer family, who had invasive ductal breast carcinomas at 39 and 42 years of age. We also identified a PALB2 p.Q775X carrier who had papillary serous ovarian cystadenocarcinoma at age 58 among the 238 serous subtype ovarian cancer cases investigated, who also had breast cancer at age 52. Conclusion Our findings, taken together with previous reports, support adding PALB2 c.2323C>T p.Q775X to the list of cancer susceptibility genes for which founder mutations have been identified in the French Canadian population.